Development of Economic Creativity of Craftsmen Woven Bags from Typical Lombok Rattan Through Digitalization of Business Management in Beleka Village - Hambali Hambali; Maspaini Maspaini; Muhamad Ahyat; Dwi Nurhidayati (Sasambo: Jurnal Abdimas (Journal of Community Service), 2023)
The Beginner Community Empowerment Program (PMP) aims to increase the knowledge and skills of craftsmen groups, with a focus on the "Bilalbeleke-art Group," which consists of eight members who are experts in making woven bags from typical Lombok rattan. This group of partners often faces a number of problems in running their business, especially related to organizational management, finance and marketing. In addition, they face challenges in production, including design and production equipment, as well as business and marketing planning, especially in the use of information technology. Therefore, implementing this activity is very important to overcome the problems faced by these partners. Thus, the main aim of this program is to solve the problems faced by partner groups and simultaneously empower them through the development of the creative economy.